Incidence of lymphoma in HIV-HCV-infected patients. Modifications in function of the anti-hepatitis C virus therapy. - Gutiérrez-Saborido, D.; Gutiérrez-Valencia, A.; González-Doménech, Carmen María; López Ruz, Miguel Ángel; Raffo Márquez, Miguel; Omar, Mohamed; Girón-González, José Antonio; Grupo de Estudio de Hepatitis Virales (HEPAVIR) of the Sociedad Andaluza de Enfermedades Infecciosas (SAEI) (Springer, 2019)
The change in the incidence of lymphomas in function of the presence or absence of sustained virological response after anti-hepatitis C therapy in a cohort of human immunodeficiency (HIV)-hepatitis C (HCV) viruses coinfected patients was analyzed. A prospective cohort of 755 HIV-HCV coinfected patients who received their first anti-HCV therapy, based on interferon + ribavirin schemas, was evaluated. Incidence and histologic types of lymphomas were analyzed in two periods: (1) before administration of anti-HCV therapy and (2) after anti-HCV therapy. The association between lymphoma incidence and demographic, HIV- (minimum CD4+ cell count and CD4+ cell count at diagnosis of lymphoma, antiretroviral therapy, maximal HIV load and HIV load at diagnosis of lymphoma) and HCV-related variables (HCV load, genotype, sustained viral response to anti-HCV therapy) were analyzed. A total of 13 lymphomas [incidence rate (95% confidence interval), 0.72 (0.33-1.11) × 1000 person-years, time from HIV diagnosis to lymphoma diagnosis (median, interquartile range), 15 (11-19) years] were diagnosed. Nine of them were non-Hodgkin and four Hodgkin lymphomas. The median CD4+ T cell count at diagnosis of lymphoma was 457/mm3, with only two cases with values lower than 200/mm3. The incidence rate of non-Hodgkin lymphomas was similar pre- and post-anti HCV therapy [0.33 (0.00-0.65) vs 0.68 (0.08-1.26) × 1000 person-years, respectively, p > 0.05]. Patients with sustained virologic HCV response showed similar incidence rate of lymphomas than that of those without anti-HCV response. In conclusion, anti-HCV therapy does not modify the incidence rate of lymphomas in HIV-HCV coinfected patients.
Keywords: Linfomas; SIDA Usado p; Virus de la hepatitis C; HIV; Hepatitis C virus; Hodgkin lymphoma; Interferon alpha; Non-Hodgkin lymphoma; Ribavirin